Cyclin D1 expression in prostate carcinoma - Pereira,R.A. (2014)
The purpose of this study was to investigate the relationship between cyclin D1 expression and clinicopathological parameters in patients with prostate carcinoma. We assessed cyclin D1 expression by conventional immunohistochemistry in 85 patients who underwent radical prostatectomy for prostate carcinoma and 10 normal prostate tissue samples retrieved from autopsies. We measured nuclear immunostaining in the entire tumor area and based the results on the percentage of positive tumor cells. The preoperative prostate-specific antigen (PSA) level was 8.68±5.16 ng/mL (mean±SD). Cyclin D1 staining was positive (cyclin D1 expression in >5% of tumor cells) in 64 cases (75.4%) and negative (cyclin D1 expression in ≤5% of tumor cells) in 21 cases (including 15 cases with no immunostaining). Normal prostate tissues were negative for cyclin D1. Among patients with a high-grade Gleason score (≥7), 86% of patients demonstrated cyclin D1 immunostaining of >5% (P<0.05). In the crude analysis of cyclin D1 expression, the high-grade Gleason score group showed a mean expression of 39.6%, compared to 26.9% in the low-grade Gleason score group (P<0.05). Perineural invasion tended to be associated with cyclin D1 expression (P=0.07), whereas cyclin D1 expression was not associated with PSA levels or other parameters. Our results suggest that high cyclin D1 expression could be a potential marker for tumor aggressiveness.